A band-selective low-noise amplifier using an improved tunable active inductor for 3–5 GHz UWB receivers. (July 2017) - Shim, Jaemin; Jeong, Jichai
Abstract: We propose a three stage 3–5 GHz band-selective ultra-wideband low noise amplifier (LNA). A capacitor cross-coupled gm -boosting broadband input stage is adopted for input matching and high gain, and also improves the noise figure (NF) and reduces current consumption. The noise performance of the LNA is improved significantly using a noise cancelation stage. A band-selective stage using a proposed tunable active inductor controls input and output matching simultaneously using one output stage tuning circuit. The key aspect of the proposed active inductor is reduced interference, noise, and complexity problems encountered with conventional wide input-tunable output and input tuning architectures. We use a variable capacitor to further improve noise performance, the quality factor, and inductance of the active inductor and to provide a wide frequency tuning range. The simulation results show gains of 12.7, 13.3, and 13.3 dB, and NF values of 3.2, 3.4, and 3.7 dB at the 3.432, 3.960, and 4.488 GHz frequency bands, respectively. The proposed band-selective LNA consumes 8.4 mW from a 1.8-V power supply. Graphical abstract: Highlights: A band-selective high gain and low power dissipation UWB LNA is proposed. One stage tunable active inductor controls input and output matching simultaneously. The circuit reduces the number of inductors. Transconductance boosting method reduces power consumption. Noise canceling technique eliminates dominant thermal noise.